Affect in Peer Group Learning During Virtual Science Inquiry: Insights From Self-Reports and Video Observations - Pietarinen, Tarja; Volet, Simone; Lehtinen, Erno; Vauras, Marja (Frontiers in Psychology, 2020)
The purpose of this study was to explore affect in small groups learning together face-to-face in a virtual learning environment. The specific aims of the study were to establish how affect within groups (valence, intensity) related to the quality of group outcome (high, average, low), and to capture individual differences within the groups by using a multimethod approach. Participants were six groups of three high school students (N = 18) who achieved distinct outcome levels. Students’ self-reports of their affect and observed affect (researcher-coded selected segments from videos) were used to examine affect during three phases of interdisciplinary science inquiry, namely, planning the experiment, experimenting in the virtual laboratory, and concluding and preparing a joint group presentation. The overall results showed that positive affect was prevalent in both self-reports and researcher-coded observations across all phases. However, while self-reports displayed a strong dominance of positive affect, there was more variation in observed affect. Furthermore, the intensity of affect was higher in self-reports than in observations, for both positive and negative affect. Nonetheless, no effect of affect on group outcome was found. Finally, while within-group consistency in affect was evident in the extreme groups (high, low performance), it was more ambivalent in the groups that achieved an average performance. The results are discussed in light of the literature, and directions for future research on affect in collaborative learning are proposed.